Jerarquías Una escritura del espacio - Santos Guerrero, JULIÁN (Escritura e Imagen, 2005)
From a Jacques Derrida thought: «Architecture is the script (writing) of space, a way to open space for the event so as to allow it to take place», the present article inquires into language and architecture relationship, being the author convinced that architecture is related to making things happen, allowing them to take their place into being, and also with the realization (occurrence) of sense in conjunction with space accomplishment abilities. Even though, so in architecture as it is in writing, there is something that does not belong to space, something which does not consume, staying unfinished and open: a future, something which is unfinished and due to this, given to interpretation, to the symbol; and at the same time, a resistance or a reluctant memory to come into presence, to sense, to logos, or to any other way of order, or exact and clear formulation in a statement. A confusion in sense origin and therefore, also a ruin. This is the irreducible symbolical character of architecture and its poetical moment. Thus far, the point is trying to see and understand construction not from harmony or pleasing combination, not from symmetry of suitable fitting, but from the condition of that all, and so, from a certain impossibility and, in consequence, from a gap, a half-way, an interval, the spreading-out, the necessary disorder or imbalance that supports every construction, the strangeness that any building gives shelter to.